واقع العلاقة بين آليات حوكمة الشركات والأداء المالي: دراسة حالة البنك التجاري الكويتي (2010-2017) - صحراوي، جليلة; جديدن، لحسن (المركز الجامعي بلحاج بوشعيب عين تموشنت - معهد العلوم الاقتصادية، التسيير والعلوم التجارية, 2017)
تهدف هذه الدراسة إلى إبراز دور وأهمية آليات حوكمة الشركات على الأداء المالي، وواقع تطبيقها، من خلال تجسيد مجموعة من المؤشرات واستكشاف أثرها نظريا، وتطبيقيا على مستوى البنك التجاري الكويتي، واستخراج أهم النتائج خلال فترة الدراسة 2010- 2017 تبين لنا من الدراسة اعتماد الباحثين على آليات مختلفة لحوكمة الشركات وعدم إجماعهم على مؤشرات موحدة ومحددة، حيث أثر تطبيقها على الأداء المالي للشركات يختلف من بلد لآخر ومن شركة لأخري، وعلى مستوى البنك التجاري الكويتي، فقد تبين التزام البنك بتعليمات وممارسات حوكمة الشركات واستناده في ذلك بدرجة كبيرة إلى نظرية الوكالة، وحيث كانت نتائج أدائه المالي جد محفزة، ليتضح من خلالها أن الهيكل الناجح لحوكمة الشركات هو أساس خلق القيمة والتميز في الأداء والكفاءة.
This study aims to highlight the role and importance of the corporate governance mechanisms on financial performance, the reality of its application, through a set of indicators and explore their impact theoretically, and applied at the level of the Commercial Bank of Kuwait, and extracting the most important results during the study period 2010-2017. The study shows that researchers rely on different mechanisms of corporate governance and do not agree on unified and specific indicators, where their impact on the financial performance of companies varies from country to country and from company to company, at the level of Commercial Bank of Kuwait, the Bank's compliance with corporate governance guidelines and practices has been demonstrated to a large extent by the Agency's theory, And where the results of its financial performance are very motivating, showing that the successful structure of corporate governance is the basis for creating value and excellence in performance and efficiency
Keywords: سياسة الحوكمة -- الأداء المالي -- الأداء المالى -- البنك التجارى -- الكويت